A Dicyanomethylene‐Substituted Triangulene: Effects of Molecular‐Symmetry Reduction and Electron‐Accepting Substituents on a Fused Polycyclic Neutral π‐Radical System. Issue 9 (11th June 2013) - Ueda, Akira; Wasa, Hideki; Nishida, Shinsuke; Kanzaki, Yuki; Sato, Kazunobu; Takui, Takeji; Morita, Yasushi
Abstract A triangulene‐based C2‐symmetric 33 π‐conjugated stable neutral π‐radical, 2., which possesses two dicyanomethylene groups and one oxo group, has been designed, synthesized, and isolated as an analogue of tris(dicyanomethylene) derivative 1. and trioxo derivative TOT. with C3 symmetry. Effects of molecular‐symmetry reduction and electron‐accepting substituents on this fused polycyclic neutral π‐radical system were studied in terms of their molecular structure, electronic‐spin structure, and electrochemical and optical properties with the help of theoretical calculations. Interestingly, this system (2.) has a four‐stage redox ability, like TOT., as well as low frontier energy levels and a small SOMO–LUMO gap, similar to 1., in spite of the loss of the degenerate LUMOs in symmetry‐lowered 2., which is associated with the attachment of the weaker electron‐accepting oxo group instead of the dicyanomethylene group in 1.. These prominent results are attributable to the structural and electronic properties in the triangulene‐based highly delocalized fused polycyclic neutral π‐radical system.